1996
DOI: 10.1111/j.1442-200x.1996.tb03456.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term ventilator‐assisted children in Japan: A national survey

Abstract: Owing to improved technology and care for patients who need mechanical ventilation, the quality of life as well as the prognosis for long‐term ventilator‐assisted patients has improved significantly in recent years. However, the increased number of these patients has raised economic, ethical and medical problems. In order to assess the magnitude of these problems, we conducted the first nationwide survey on the status of long‐term ventilator‐assisted children in Japan. Questionnaires were mailed to 2524 pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…Authors from several countries have described their experience with home‐based ventilation programmes for children . In Australia and New Zealand, guidelines for home ventilation in children were recently published, adding to those published in the United Kingdom (1998) and in the USA (1990) .…”
Section: Do We Really Know the Size Of The Problem?mentioning
confidence: 99%
“…Authors from several countries have described their experience with home‐based ventilation programmes for children . In Australia and New Zealand, guidelines for home ventilation in children were recently published, adding to those published in the United Kingdom (1998) and in the USA (1990) .…”
Section: Do We Really Know the Size Of The Problem?mentioning
confidence: 99%
“…11 Despite this there is limited information specifically on children at home on ventilation via a tracheostomy and their long term outcomes. The largest prospective study from France reported on outcomes of a heterogeneous group of children, and only 16 of the 158 on mechanical ventilation were supported via tracheostomy.…”
Section: Comparative Experiencesmentioning
confidence: 99%
“…A nationwide survey on the status of long‐term ventilator‐assisted patients in Japan has revealed that 55 patients with WHD received long‐term ventilator support in Japan. 5 This is quite contrary to the situation in some European countries, for example, in Italy where few patients with WHD are given mechanical ventilation. 6 …”
mentioning
confidence: 90%